Coping Mechanism in Cancer Patients Undergoing Chemotherapy at Santa Elisabeth Hospital Medan in 2024 - Ginting, Friska Sri Handayani; Pakpahan, Rotua Elvina; Zebua, Srifaniat (JURNAL KEBIDANAN, KEPERAWATAN DAN KESEHATAN (BIKES), 2025)
Coping mechanisms are strategies individuals use to address challenges, both cognitively and behaviorally. This study aims to identify the coping mechanisms employed by cancer patients undergoing chemotherapy at Santa Elisabeth Hospital Medan in 2024. A descriptive research design was used with an accidental sampling method, involving 42 respondents. Data collection was conducted using the Ways of Coping questionnaire. The results revealed that the majority of respondents (88.1%, or 37 individuals) utilized maladaptive coping mechanisms, while only 11.9% (5 individuals) demonstrated adaptive coping strategies. Maladaptive coping mechanisms were characterized by emotional distress, frustration, and avoidance behaviors, which negatively impacted patients' psychological well-being. Conversely, patients who exhibited adaptive coping mechanisms tended to accept their condition and actively engage in positive coping strategies. The findings suggest that the emotional and psychological burden of chemotherapy significantly affects coping behaviors, with most patients struggling to adapt effectively.These results emphasize the need for healthcare professionals to provide psychological support and interventions aimed at promoting adaptive coping strategies. Future research should explore factors influencing coping mechanisms and the role of supportive care in enhancing cancer patients' quality of life